2018
DOI: 10.1016/j.scitotenv.2018.03.380
|View full text |Cite
|
Sign up to set email alerts
|

Fading positive effect of biochar on crop yield and soil acidity during five growth seasons in an Indonesian Ultisol

Abstract: Low fertility limits crop production on acidic soils dominating much of the humid tropics. Biochar may be used as a soil enhancer, but little consensus exists on its effect on crop yield. Here we use a controlled, replicated and long-term field study in Sumatra, Indonesia, to investigate the longevity and mechanism of the effects of two contrasting biochars (produced from rice husk and cacao shell, and applied at dosages of 5 and 15tha) on maize production in a highly acidic Ultisol (pH3.6). Compared to rice h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0
25

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(109 citation statements)
references
References 48 publications
7
77
0
25
Order By: Relevance
“…This suggested that addition of both dolomite and biochar may not be good and could lead to loss of functional properties of biochar in the subsequent cropping although this hypothesis remains untested. However, Cornelissen et al [30] reported that rice husk biochar addition on acidic Ultisol soil of Indonesia showed a less pronounced effect on the soil pH as the cropping season increased due to decreasing liming potential, which also agrees with our result. In addition to pH, biochar addition showed tendency to increase soil EC especially in the second cropping that could be attributed to the highly soluble minerals contained in the rice husk biochar that was readily added into the soil.…”
Section: Effect Of Biochar On Soil Physico-chemical Properties In Firsupporting
confidence: 92%
See 2 more Smart Citations
“…This suggested that addition of both dolomite and biochar may not be good and could lead to loss of functional properties of biochar in the subsequent cropping although this hypothesis remains untested. However, Cornelissen et al [30] reported that rice husk biochar addition on acidic Ultisol soil of Indonesia showed a less pronounced effect on the soil pH as the cropping season increased due to decreasing liming potential, which also agrees with our result. In addition to pH, biochar addition showed tendency to increase soil EC especially in the second cropping that could be attributed to the highly soluble minerals contained in the rice husk biochar that was readily added into the soil.…”
Section: Effect Of Biochar On Soil Physico-chemical Properties In Firsupporting
confidence: 92%
“…The total monthly rainfall received in the region in 2017 were 66.5, 158.5, 161 and 224.5 mm in June, July, August and September respectively. The average daily maximum temperatures were 24.2 • C in June, 30.6 • C in July, 30.5 • C in August and 26.0 • C in September favorable for sesame growing. The region has primarily one sesame crop harvested per year.…”
Section: Experiments Sitementioning
confidence: 96%
See 1 more Smart Citation
“…Biochar at smaller rates usually tend to have positive effects on germination. In general, biochar amendments provide a better soil environment and increase soil pH to a favorable range to promote greater germination (Cornelissen et al, 2018). Increased germination with biochar is often considered a positive predictor for biochar impact on plant growth (Solaiman et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…For acidic and highly weathered tropical soils with similar characteristics as our experimental soil, crop performance when the soil is amended with biochar is often linked with increases in SOC and pH (Cornelissen et al, ; Crane‐Droesch, Abiven, Jeffery, & Torn, ). Results from our study confirm this assertion as B 30 significantly increased SOC and pH relative to B 0 .…”
Section: Discussionmentioning
confidence: 99%